ANALISIS SIKAP KERJASAMA SISWA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA MELALUI MODEL KOOPERATIF LEARNING - Mandasari, Sefira Dwi; Supriyadi, Supriyadi (Universitas Muria Kudus, 2024)
Aim of this research is to find out to what extent an attitude of cooperation can be carried out using the cooperative learning model when learning Pancasila education in class IV at SDN Watesnegoro 2, academic year 2023/2024.Method used in this research is qualitative with a descriptive approach. This research was carried out at SDN Watesnegoro 2 on March 25-March 30. The subjects used in this research were class teachers and class IV students. The data collection technique in this research uses data triangulation techniques. Data analysis is used through observation and interviews as well as documentation to present data and draw conclusions from research results.The research results reveal that the cooperative attitude can run well and smoothly and the impact provided by the cooperative learning model can improve the quality of students' ability to collaborate. The application of the cooperative learning model through activities in the classroom includes conveying learning objectives, delivering material, group division, working on group assignments, group presentations providing feedback and giving rewards. Not only that, through the cooperative learning model, students can increase their own experience and develop a caring attitude towards other students, so that they can train students' fast and slow responses in groups.